THE DESCRIPTION OF LION ZOOSEMY IN UZBEK’S NOVELS (American Journal of Research in Humanities and Social Sciences, 2023)
The image of a lion is distinguished by its characteristics and features in Uzbek novels. Especially, the zoosemy of lion means courage, bravery, fearlessness, gallantry, loyalty to one's partner,while attacking to any other anmals ,he retreat first,then attacking with furiosity. At the same time, these qualities are transferred to human characteristics through the lion. The comparison of the animal character with the human one is the motivation to reveal the zoosemy of the lion in the novels. This article discusses the nature of the lion through the writing style of writers.Each uzbek writer used the personality of lion zoosemy with different ways.